Meta-Analysis’ Validity of Booklet on the Human Reproductive System as a Supplementary Biology Teaching Material for High School - Rizki, Muaddiyatur; Fitri, Rahmadhani (Bioilmi: Jurnal Pendidikan, 2024)
Reproductive system disorders or diseases threaten Indonesia's young generation, so prevention is necessary before they occur. One way that can be done is by adding preventive value information to learning. Booklet learning media can help convey preventive information. The research aims to analyze the level of validity of booklet media using the meta-analysis method, namely a systematic and quantitative assessment of previous research. Data collection was carried out by searching for articles from previous researchers in the thesis database of the UNP Biology Department and by accessing several journals on the internet. The population in this study were all documents related to booklets, and the sample used in this study consisted of 15 articles and theses. The research results show that the average validity value of booklet media development in the content component is 90.93%, linguistics 89.43%, presentation 85.38%, and graphics 90.89%. Overall, the average validity of the booklet is 89.19% in the very valid category. From these results, the booklet media can be developed and is suitable for use in the biology learning process on reproductive system material.